Cardiac Magnetic Resonance Strain in Beta Thalassemia Major Correlates with Cardiac Iron Overload - Deidra Ansah; Nazia Husain; Alexander Ruh; Haben Berhane; Anthony Smith; Alexis Thompson; Andrew De Freitas; Cynthia K. Rigsby; Joshua D. Robinson (Children, 2023)
Background: Beta thalassemia major (Beta-TM) is an inherited condition which presents at around two years of life. Patients with Beta-;TM may develop cardiac iron toxicity secondary to transfusion dependence. Cardiovascular magnetic resonance (CMR) T2*, a technique designed to quantify myocardial iron deposition, is a driving component of disease management. A decreased T2* value represents increasing cardiac iron overload. The clinical manifestation is a decline in ejection fraction (EF). However, there may be early subclinical changes in cardiac function that are not detected by changes in EF. CMR-derived strain assesses myocardial dysfunction prior to decline in EF. Our primary aim was to assess the correlation between CMR strain and T2* in the Beta-TM population. Methods: Circumferential and longitudinal strain was analyzed. Pearson’s correlation was calculated for T2* values and strain in the Beta-TM population. Results: We identified 49 patients and 18 controls. Patients with severe disease (low T2*) were found to have decreased global circumferential strain (GCS) in comparison to other T2* groups. A correlation was identified between GCS and T2* (r = 0.5; p < 0.01). Conclusion: CMR-derived strain can be a clinically useful tool to predict early myocardial dysfunction in Beta-TM.